PENGARUH PEMIMPIN TERHADAP KEBERHASILAN PENANAMAN GEREJA MENURUT KITAB KISAH PARA RASUL - Yohanes Gijs Pany (EKKLESIA: Jurnal Teologi dan Pendidikan Kristiani, 2026)
Abstract: Leadership is the key to the progress of an institution, including the church as a ministry institution. Weak church leadership will have a negative impact on church development. The early church, which the book of Acts states is a model for today's church in terms of its growth strategies, Theologically, the growth of the early church was the work of the Holy Spirit pouring out His power. The book Acts 1:8 expresses it this way: "But you will receive power when the Holy Spirit has come upon you, and you will be My witnesses in Jerusalem and in all Judea and Samaria and to the ends of the earth.". However, in terms of management and ministry of the church as an institutional organization, of course, the 'leadership' carried out by the Apostles can also be a model for church leadership today. Abstrak: Kepemimpinan merupakan kunci kemajuan suatu lembaga termasuk gereja sebagai lembaga pelayanan. Lemahnya kepemimpinan gereja akan memberi dampak negatif terhadap pertubuhan gereja. Gereja mula-mula yang dinyatakan buku Kisah Para Rasul merupakan model bagi gereja masa kini dalam kiat pertumbuhannya. Secara teologis pertumbuhan  gereja mula-mula merupakan karya Roh Kudus yang mencurahkan kuasaNya.  Kitab KPR  1:8 mengungkapkannya demikian. Tetapi kamu akan menerima kuasa, kalau Roh Kudus turun ke atas kamu, dan kamu akan menjadi saksi-Ku di Yerusalem dan di seluruh Yudea dan Samaria dan sampai ke ujung bumi. Namun demikian dari segi management dan pelayanan gereja sebagai organisasi kelembagaan tentu ‘kepemimpinan‘ yang diemban para Rasul juga bisa menjadi model kepemimpnan gereja masa kini.